2018
DOI: 10.1109/tbme.2018.2797239
|View full text |Cite
|
Sign up to set email alerts
|

Ballistocardiogram-Based Approach to Cuffless Blood Pressure Monitoring: Proof of Concept and Potential Challenges

Abstract: The proposed approach has potential to complement the pulse transit time technique for cuffless blood pressure monitoring in two ways. First, it may be integrated with pulse transit time to enable independent monitoring of diastolic and systolic pressures via the J-K amplitude. Second, it may even enable diastolic and systolic pressure monitoring from the ballistocardiogram alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 26 publications
2
56
0
1
Order By: Relevance
“…However, our study, instead, suggests that it may be necessary to obtain innovative PTTs to improve the correlation with BP via novel sensors and/or waveform detections. Innovative sensors may include ballistocardiography 16 , seismocardiography 17 , 18 , wrist bioimpedance 19 , ultrasound 20 , and radar sensors 21 . Unlike ECG and PPG waveforms, these sensors may afford true PTT rather than dPTT or PAT.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study, instead, suggests that it may be necessary to obtain innovative PTTs to improve the correlation with BP via novel sensors and/or waveform detections. Innovative sensors may include ballistocardiography 16 , seismocardiography 17 , 18 , wrist bioimpedance 19 , ultrasound 20 , and radar sensors 21 . Unlike ECG and PPG waveforms, these sensors may afford true PTT rather than dPTT or PAT.…”
Section: Discussionmentioning
confidence: 99%
“…Although PAT or PTT based approach for continuous BP monitoring has already shown remarkable progress through numerous studies [8,10,14,19,[21][22][23][24], it has not yet been widely accepted for ubiquitous NCBPM due to its limited accuracy. One of the reasons for this may be that PAT alone cannot fully reflect the complex BP dynamics and that conventionally measured PAT in ubiquitous BP monitoring involves PAT measured at peripheral arteries rather than central arteries.…”
Section: A Ppg Morphology Features As Predictors Of Bp In Ubiquitousmentioning
confidence: 99%
“…PAT is defined as the time difference between the R-peak of the electrocardiogram (ECG) and a point on distal pulse waveform such as the photoplethysmogram (PPG) measured at the fingertips. Although some studies have shown remarkable results in NCBPM using PAT and/or PTT methods [8,10,14,21,22], the results are still widely varied in terms of accuracy [19,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is necessary to press the finger manually to apply the oscillometric principle, recent studies have shown potential to use smartphones as blood pressure monitors [34, 35]. Among the nonocclusive techniques, tonometry [3638], pulse wave velocity (PWV) [3950], and photoplethysmography (PPG) [51, 52] have been extensively studied and developed for ambulatory blood pressure monitoring (ABPM).…”
Section: Discussionmentioning
confidence: 99%